Challenges in achieving the guideline-recommended amikacin level for Mycobacterium avium complex pulmonary disease - Takuya Akutsu; Kazuya Tone; Airi Hasegawa; Takaaki Kitayama; Shunsuke Inaki; Mina Gochi; Masamichi Takagi; Jun Araya (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: The addition of aminoglycosides to a macrolide-based regimen is recommended for refractory Mycobacterium avium complex pulmonary disease (MAC-PD). For intravenous amikacin (AMK) administration three times a week, the ATS/ERS/ESCMID/IDSA guidelines recommend targeting a peak serum concentration of 65–80 µg/mL. However, the feasibility of achieving the guideline-recommended AMK concentration remains unclear. Methods: From 2018 to 2022, we retrospectively analyzed patients with refractory MAC-PD treated with AMK thrice weekly for ≥3 months combined with an oral regimen of ≥2 drugs, including macrolides. The peak serum concentration and therapeutic effects of AMK were evaluated. Results: The median age of the 9 patients was 70 years (range: 50–79 years; 2 men and 7 women). The causative organism was M. avium in all cases. All cases demonstrated susceptibility to AMK, which was administered at a median dose of 700 mg/day (15.8 mg/kg/day) for a median duration of 6 months. One patient experienced hearing loss, which led to AMK discontinuation at 4 months. The median AMK peak concentration was 47.1 μg/mL, with a tendency to be higher in the clinical efficacy group compared to the nonefficacy group. None of patient, except one, achieved the target AMK peak concentration. Conclusions: In this preliminary study, the guideline-recommended AMK concentration for MAC-PD was not achieved in the majority of patients. Due to the small sample size and retrospective design, robust conclusions regarding the association between AMK concentrations and clinical outcomes could not be drawn. Prospective randomized controlled trials are required to better define the optimal AMK concentration for efficacy and safety. Trial registration: Not applicable.